2019
DOI: 10.1111/tbed.13415
|View full text |Cite
|
Sign up to set email alerts
|

Rabies surveillance in wild mammals in South of Brazil

Abstract: The sylvatic cycle of rabies, caused by the Rabies lyssavirus (RABV), is maintained in the American Continent by aerial and terrestrial wild mammals. In this study, we combined passive surveillance of rescued wild animals with active serological surveillance in targeting areas at Rio Grande do Sul State and Santa Catarina State, south of Brazil, where bites of humans by wild animals have been reported. Circulation of RABV in Brazilian bats has been extensively demonstrated; however, the observation of such inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In particular, most human deaths and livestock losses from rabies in the continent are now attributed to spillover from vampire bats, Desmodus rotundus ( 6 8 ). Foxes (specifically the crab-eating fox Cerdocyon thous ) and primates (specifically the marmoset Callithrix jacchus ) are also considered reservoirs of specific RABV variants ( 9 12 ), while serological studies show evidence of rabies exposure in several other primate and marsupial species but without evidence of clinical infections ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, most human deaths and livestock losses from rabies in the continent are now attributed to spillover from vampire bats, Desmodus rotundus ( 6 8 ). Foxes (specifically the crab-eating fox Cerdocyon thous ) and primates (specifically the marmoset Callithrix jacchus ) are also considered reservoirs of specific RABV variants ( 9 12 ), while serological studies show evidence of rabies exposure in several other primate and marsupial species but without evidence of clinical infections ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In large and biodiverse countries such as Brazil, rabies circulates among a wide range of wild species including bats, primates, and foxes, complicating the establishment of preventative measures aiming to limit rabies spillover to humans and domestic animals ( 15 17 ). The high cost and current uncertainties in the interpretation of serological data among wildlife has restricted the implementation of serology to a small number of wild populations and specific regions of the country ( 12 ). In the Northeast region, crab-eating fox and bats have been frequently found exposed or infected, while transmission of RABV from foxes to domestic dogs has been reported ( 16 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, RABV was controlled in domestic dogs by intense public vaccination campaigns (Freire de Carvalho et al, 2018). However, the circulation of RABV in wildlife has become a major concern for public health (Antunes et al, 2018;Campos et al, 2019;Rocha et al, 2017), where biting of humans by wild animals has been reported. Moreover, crabeating foxes were identified as reservoirs of RABV variants (Campos et al, 2019;Rocha et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Titres ≤ 0.1 IU/ml were considered RVNA‐negative and > 0.1 IU/ml were considered RVNA‐positive. Other serology studies in wildlife have used similar thresholds to detect RVNA (Araujo et al., 2014; Campos et al., 2019; Marcelo Azevedo de Paula Antunes et al, 2017; Silva et al., 2010). To predict RVNA titres, a GLMM with a log‐normal distribution was fit to the infected cell counts across the SRIG concentration series.…”
Section: Methodsmentioning
confidence: 99%